Pore structure improvement in cermet for anode-supported protonic ceramic fuel cells - Park, Yu-Eun; Ji, Ho-Il; Kim, Byung-Kook; Lee, Jong-Ho; Lee, Hae-Weon; Park, Jong-Sung (ELSEVIER SCI LTD, 2013)
The porous cermet of Yb-doped BaZrO3 and nickel (BZYb-Ni) for anode-supported protonic ceramic fuel cells (PCFCs) was fabricated by compression molding following the liquid condensation process (LCP). The gas permeability of BZYb-Ni produced by LCP (BZYb-Ni-LCP) was greater than that of BZYb-Ni produced by a conventional drying method (BZYb-Ni-CDM) although their porosities were similar. The greater permeability of BZYb-Ni-LCP than that of BZYb-Ni-CDM is consistent with more efficient structures for gas flow; a smaller specific surface area, and a larger critical diameter for pores in BZYb-Ni-LCP than those for pores in BZYb-Ni-CDM. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: ELECTRICAL-CONDUCTIVITY; MICROSTRUCTURE; CONDUCTORS; STABILITY